Health-related Quality of Life and hospital costs of Finnish melanoma patients participating in the second Multicenter Selective Lymphadenectomy Trial (MSLT-II) - Pia J. Heino; Jukka Pappinen; John F. Thompson; Micaela Hernberg; Tiina A. Jahkola; Mark B. Faries (Acta Oncologica)
Background and purpose: After reports that complete lymph node dissection (CLND) did not improve melanoma-specific survival of sentinel lymph node (SLN)-positive patients, the use of CLND has diminished but it is still carried out for selected patients. We sought to assess differences in Health-Related Quality of Life (HRQoL) and tertiary care costs among the Finnish Multicenter Selective Lymphadenectomy Trial (MSLT)-II-patients.